In vivo detection of iron and neuromelanin by transcranial sonography: A new approach for early detection of substantia nigra damage - Zecca, Luigi; Berg, Daniela; Arzberger, Thomas; Ruprecht, Petra; Rausch, Wolf D.; Musicco, Massimo; Tampellini, Davide; Riederer, Peter; Gerlach, Manfred; Becker, Georg (Movement disorders, 2005)
Early diagnosis of Parkinson's disease (PD) in nonsymptomatic patients is a key issue. An increased echogenicity of the substantia nigra (SN) was found previously in Parkinsonian patients and in a low percentage of healthy adults. These nonsymptomatic subjects also showed a reduced 18F‐dopa uptake in striatum, suggesting a preclinical injury of the nigrostriatal system that could later proceed into PD. To investigate the ability of ultrasonography to detect markers of SN degeneration, such as iron deposition and neuromelanin depletion, we scanned postmortem brains from normal subjects at different ages by ultrasound and measured the echogenic area of the SN. The SN was then dissected and used for histological examinations and determination of iron, ferritin, and neuromelanin content. A significant positive correlation was found between the echogenic area of the SN and the concentration of iron, H‐ and L‐ferritins. Multivariate analysis carried out considering the iron content showed a significant negative correlation between echogenicity and neuromelanin content of the SN. In PD, a typical loss of neuromelanin and increase of iron is observed in this brain area. The finding of a positive correlation between iron and ferritin levels and a negative correlation of neuromelanin content with the area of echogenicity at the SN could therefore provide an interesting basis for diagnosis and therapeutic follow‐up studies in PD. © 2005 Movement Disorder Society